A revision of the genus Rhynchostegiella (Brachytheciaceae) in the Iberian Peninsula and Balearic Islands - Guerra, Juan; Ríos, Diana; Gallego, María Teresa (Phytotaxa, 2014)
The moss genus Rhynchostegiella (Brachytheciaceae) is taxonomically revised for the Iberian Peninsula and Balearic Islands based on morphological data. After a thorough revision of both herbarium material and our own recent collections from the area, we recognize five Iberian species of the genus. A key, descriptions, illustrations and distribution data are provided for the species. The record for Rhynchostegiella bourgaeana in Europe, in Cadiz, Spain, is confirmed.